EFEKTIVITAS MEDIA POP UP BOOK PADA PELAJARAN BAHASA INDONESIA UNTUK MENGEMBANGKAN LITERASI SISWA KELAS RENDAH - Kristia Setyaningsih; Arri Handayani (STKIP Subang, 2023)
Pop-Up Book is a book with three-dimensional elements that have parts that can move, also provide surprises in every opening of the page, the display of images that are upheld emits an active image display that it gives a new impression and can be interesting and provides entertainment in readinghis. This article aims to present a literature review from various sources about the use of pop-up book learning media in the Indonesian learning process. From the results of the literature review, it shows the effectiveness of using pop-up book media in Indonesian lessons to develop literacy of low-grade students. This is shown by students' interest in opening and seeing a story so that students indirectly increase their reading literacy and stimulate students' thinking.